Sustainable development of China’s aesthetic teaching in long-term policy changes - Xuebing Wang; Xiaohui Chen; Pengxi Qin; Jia Lu; Hanxi Wang (PLoS ONE, 2025)
The construction level of the teaching staff in aesthetic education determines the education quality, and relevant policies are the guarantee for the teaching staff construction. Due to multiple factors, the scientific formulation of aesthetic education policies in China is difficult and complex. The study objective is to enhance the role of policy in the teaching staff construction. This study was based on the theories proposed by MacDonald and Elmore, and 58 out of 1644 policy documents on the teaching staff construction in aesthetic education from 1978 to 2023 were selected to construct a two-dimensional analysis framework centered on policy instruments. The study indicated that the construction policy of China’s teaching staff in aesthetic education focused on professional development, the level of issue institutions was constantly improving, and policy coordination was constantly enhancing. The application ratio of different policy instruments was unbalanced. The content distribution of China’s aesthetic education policy was unbalanced. The selection of policy instruments by the Chinese government had a high degree of compatibility with policy content. This study provides reference for formulating scientific policies in the construction of the aesthetic education teacher team.